Protective Effects of Exercise Training Against Aged-Induced the Reduction of Cardiac Angiogenic Capacity in Middle-Aged Rats - Mekrungruangwong, Titiporn; Kasetsuwan, Pimpetch; Viboolvorakul, Sheepsumon; Patumraj, Suthiluk (Cardiology and Cardiovascular Medicine, 2020)
Objective: To investigate the protective effects of exercise training against aged-induced the reduction of cardiac angiogenic capacity associated with VEGF, phospho-Akt1, and eNOS in middle-aged rat hearts. Methods: Rats were divided into three groups: Sedentary - young group (aged 4 months), Sedentary - middle-aged sham group (aged 14 months), and Exercise-trained middle-aged group. In the younger group, rats were subjected to the same swim environment as the trained-aged animals, except they were remained freely in their cages. In sham group, rats were immersed in cylindrical tanks filled with water to a depth of 5 cm that controlled temperature at 33-36 oC for 30 minutes/day, 5 days/week for 8 weeks. In Exercise trained – middle-aged group, rats swam in cylindrical tanks filled with water to depth of 50-55 cmcontrolled temperature at 33-36 oC for 60 minutes/day, 5 days/week for 8 weeks. To evaluate the malondialdehyde level (MDA), the thiobarbituric acid reactive substances assay (TBARS) were used in this study. The level of phospho-Akt1, eNOS, and VEGF in heart tissue homogenate were determined by sandwich immunoassays. Results: There were significant difference in systolic blood pressure, diastolic blood pressure and mean arterial blood pressure among the sedentary- young group and sedentary-middle aged. However, the exercise trained middle aged group showed the lower value than in the sedentary middle-aged group but not significant. The levels of phospho-Akt1, eNOS, and VEGF were significantly increased in the exercise trained middle group when compare with sedentary - middle aged groups. Conclusion: The present study demonstrated that the protective effect of exercise training on age-induced cardiac microvascular changes are involved the upregulation of VEGF eNOS and phospho-Akt1 expression in association with changes in the ROS balance.<